Quantum Philosophy : Understanding and Interpreting Contemporary Science - Omnes, Roland (Book collections on Project MUSE., 1999)
In this magisterial work, Roland Omnes takes us from the academies of ancient Greece to the laboratories of modern science as he seeks to do no less than rebuild the foundations of the philosophy of knowledge. One of the world's leading quantum physicists, Omnes reviews the history and recent development of mathematics, logic, and the physical sciences to show that current work in quantum theory offers new answers to questions that have puzzled philosophers for centuries: Is the world ultimately intelligible? Are all events caused? Do objects have definitive locations? Omnes addresses these p.